Pengaruh Motivasi, Kompetensi, Kepemimpinan, Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada PT. Herculon Carpet Semarang) - ., Linawati; ., Suhaji (Jurnal Kajian Akuntansi dan Bisnis, 2012)
This study aimed to analyze the influence of motivation, competence,leadership, and work environment on employee performance at PT. Herculon Carpet Semarang.The samples were obtained by purposive sampling method, and selected 78 respondents as asample. The analysis of data used multiple linear regression analysis which passed the classicalassumption test, multikolonierity test, autocorrelation test, heterokedastisity test, and normalitytest. In the test the coefficient of determination, the amount of adjusted R2 was 0.659, meaningthat 65.9% of the variation in changes in performance was influenced by the variable ofmotivation, competence, leadership, and work environment. While the remaining 34.1% wasinfluenced by other factors beyond the research model.In simultaneous significance test F (Ftest), f value 34.993 > F table 3.13. This means that the variable of motivation, competence,leadership, and working simultaneously had significant influence on employee performance. Inthe partial significance test (t test), motivation variable significantly influenced the performanceof employees with t value 5.589 > t table 1.9930. For variable of competence, t value -0.074 < tchart 1.9930, which means the variable of competence had no significant influence on employeeperformance. For the variable of leadership, t value 3.489 > t table at 1.9930 which means thatvariable of leadership had a significant influence on employee performance. As for the workenvironment variable, t value 1.725 < t chart 1.9930, which means that work environmentvariable had no significant influence on employee performance.Keywords: Motivation, Competence, Leadership, and work environment; employee performance